What are the health challenges an esport player faces and how can they be addressed by stakeholders? - Bullatovci, O. (International Journal of Esports, 2021)
Esports has grown aggressively in both a recreational and professional level, where millions of players are engaging daily in competitive gaming [1]. Universities are adding eSport teams and employing players at an exponential rate [2]. For example, the Chung-Ang University in South Korea accepts gamers student athletes [3]. A few esports competitions have a system that is comparable to physical sports, with professional players needing preparation and training to grow. I will be exploring the potential health challenges an esport player may face when engaging in extended sessions of virtual gaming and any prevention strategies that stakeholders can employ.